Procedural and anatomical predictors of renal denervation efficacy using two radiofrequency renal denervation catheters in a porcine model. Issue 12 (December 2018) - Wolf, Milan; Hubbard, Brad; Sakaoka, Atsushi; Rousselle, Serge; Tellez, Armando; Jiang, Xiongjing; Kario, Kazuomi; Hohl, Mathias; Böhm, Michael; Mahfoud, Felix
Abstract : Introduction: Several renal denervation (RDN) systems are currently under investigation for treatment of hypertension by ablation of renal sympathetic nerves. The procedural efficacy of devices, however, is variable and incompletely understood. This study aimed at investigating procedural and anatomical predictors of RDN efficacy by comparing two radiofrequency catheter systems in a porcine model. Methods: Domestic swine were assigned into two treatment groups ( n = 10) and one sham group ( n = 3). Bilateral RDN in main and in branch segments of renal arteries was performed using two different multielectrode catheter systems [Symplicity Spyral (SPY) and IberisBloom (IBB)]. After 7 days, measurement of norepinephrine (NEPI) tissue concentrations and histological analyses have been performed. Results: Renal NEPI tissue concentration following RDN was significantly reduced when compared with Sham (SPY: −95 ± 3% vs. Sham, P < 0.001; IBB: −88 ± 11% vs. Sham, P < 0.001). Histological evaluation showed comparable lesion depth and lesion area (lesion depth: SPY-main 6.26 ± 1.62 mm vs. SPY-branch 3.49 ± 1.11 mm; IBB-main 5.93 ± 1.88 mm vs. IBB-branch: 3.26 ± 1.26 mm, P < 0.001; lesion area: SPY-main 43.5 ± 29.5 mm 2 vs. SYP-branch 45.0 ± 38.0 mm 2 ; IBB-main 52.3 ± 34.8 mm 2 vs. IBB-branch 44.0 ± 42.6 mm 2, P = 0.77; intergroup SPY vs. IBB, P = 0.73). Histological investigations documented a significant correlation between number of ablations per millimeter length of renal artery and reduction in NEPI tissue concentration. Conclusion: The two devices under investigation demonstrated similar histopathological lesion characteristics and similar reduction of renal NEPI levels. An increase in number of ablations per millmeter length of renal artery resulted in improved efficacy and reduced variability in treatment effects.